1963
DOI: 10.1084/jem.118.6.945
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Artificial Antigens

Abstract: An effort was made to immunize guinea pigs with arsanilic acid conjugates of copolymers of D- and L-α-amino acids; ASD-GAT and ASL-GAT. An immune response was observed only in the case of ASL-GAT. Antibodies specific for the arsanilic acid hapten were produced which could also react with ASD-GAT or ASGPA. These findings indicate that the proper metabolism of the antigen may be essential to the induction of the immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

1964
1964
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 16 publications
4
10
0
Order By: Relevance
“…Since R'3 has three ABA groups on a single resorcinol nucleus, it is possible that steric interference may occur at the cellular site at which the sensitized event occurs. Previous studies confirming the work of Benacerraf et al (8) demonstrated that carriers consisting of polymers of D-amino acids did not function as antigens in producing sensitization to the ABA group. It has been suggested that the failure of such carriers to function is attributable to their indigestibility by enzymes of the reficuloendothelial system.…”
Section: Resultssupporting
confidence: 69%
“…Since R'3 has three ABA groups on a single resorcinol nucleus, it is possible that steric interference may occur at the cellular site at which the sensitized event occurs. Previous studies confirming the work of Benacerraf et al (8) demonstrated that carriers consisting of polymers of D-amino acids did not function as antigens in producing sensitization to the ABA group. It has been suggested that the failure of such carriers to function is attributable to their indigestibility by enzymes of the reficuloendothelial system.…”
Section: Resultssupporting
confidence: 69%
“…Presumably the stimulation of ABA-specific T cells by ABA-BSA might induce the release of nonspecific helper factors (10), leading to the increase observed, or two types of helper T cells like what was shown by several investigators (18,25,31) might exist. Our results with hapten conjugates of D-and i.-pclypeptides support and extend previous studies on DTH with similar materials (4,20). The failure of double conjugates of D-polymers to provide help despite their physico-chemical similarity to L-polymers suggests that they do not function as a passive bridge between T and B cell receptors.…”
Section: Discussionsupporting
confidence: 91%
“…Others have also shown that polymers of D-amino acids are non-immunogenic (15)(16)(17). These findings are compatible with our previous discussion (4,5), and the concept of others that the metabolism of the antigen (18,19), previous to the formation of the immunogenic fragment carrying the antigenic determinant, is a necessary but not sufficient cri-teflon for immunogenicity. It is believed that this cleavage may be performed by proteolytic enzymes present in macrophages (20) and may be blocked by D-amino acid polymers.…”
Section: Discussionsupporting
confidence: 89%